1996
DOI: 10.1080/10473289.1996.10467490
|View full text |Cite
|
Sign up to set email alerts
|

A Socioeconomic Assessment of Human Exposure to Ozone in the South Coast Air Basin of California

Abstract: The purpose of this study is to assess by age, race, ethnicity, and income the effects of air pollution control measures and population growth on human exposure to ozone in the South Coast Air Basin of California (SoCAB). A methodology to study human exposure to air pollutants from a socioeconomic perspective has been developed. Specifically, the Regional Human Exposure model (REHEX-II) has been applied to estimate historical (1980)(1981)(1982) and recent (1990)(1991)(1992) human exposure to ozone. The model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Consistent with the findings presented here, the proportion of upper income households and whites are higher in highozone areas downwind of New York City and Philadelphia than in the urban core where ozone precursors are emitted (Liu, 1996). Others have found that ozone levels in the South Coast are positively correlated with the percentage of whites in the community, but are inversely correlated with income (Brajer and Hall, 2005;Korc, 1996).…”
Section: Article In Presssupporting
confidence: 80%
“…Consistent with the findings presented here, the proportion of upper income households and whites are higher in highozone areas downwind of New York City and Philadelphia than in the urban core where ozone precursors are emitted (Liu, 1996). Others have found that ozone levels in the South Coast are positively correlated with the percentage of whites in the community, but are inversely correlated with income (Brajer and Hall, 2005;Korc, 1996).…”
Section: Article In Presssupporting
confidence: 80%
“…Since block group traffic density is related to vehicle emissions and was moderately correlated with the ambient concentrations of several vehicle-related pollutants, children living in these areas have higher potential for exposure. Other studies in the US have found that low-income neighborhoods and communities of color are more likely to be located near sources of pollution (Perlin et al, 1995;Korc, 1996;Neumann et al, 1998;Perlin et al, 1999Perlin et al, , 2001Morello-Frosch et al, 2002). Our results, from a large and heterogeneous state, provide further evidence that low-income and people of color are more likely to live near sources of toxic emissions, in this case freeways and major roads.…”
Section: Discussionsupporting
confidence: 70%
“…A similar evaluation conducted in Oregon found that industrial facilities were disproportionately located in minority and low-income neighborhoods, but there was no relation between hazard ranking and overall socioeconomic status (SES) of the community (Neumann et al, 1998). An assessment of ozone exposure in Southern California concluded that low-income areas generally experience higher ozone concentrations than high-income areas (Korc, 1996). Finally, a recent investigation of environmental justice in Southern California found that race and income were important predictors of estimated cancer risk based on modeled outdoor air toxics exposures from both mobile and point sources (Morello-Frosch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…34 In Los Angeles, ozone exposures during the period 1900-1992 neither were not uniformly higher among minorities than for the majority population, nor did they vary in a systematically inverse way with income. 28 While the available information, therefore, does not immediately indicate that exposure standards of the type described here would be likely to impose an inequitable ozone exposure hazard on disadvantaged populations, the issue merits further investigation.…”
Section: Topics For Further Evaluationmentioning
confidence: 99%
“…28,32,33 Secondary pollutants, such as ozone, are likely to exhibit their greatest concentrations in different areas than do primary pollutants, the concentrations of which are typically greatest in the emission source areas. Thus, the question of environmental equity must be answered specifically for each different air pollutant.…”
Section: Topics For Further Evaluationmentioning
confidence: 99%